Reducing Alternative Conception of Action-Reaction Forces: The Impact of E-Rebuttal Texts After Learning and Over Time - Fratiwi, Nuzulira Janeusse; Suhandi, Andi; Nurdini, Nurdini; Feranie, Selly; Linuwih, Suharto; Samsudin, Achmad; Susilowati, Nur Endah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
The goal of this study was to reduce students' alternative conceptions (misconceptions) of action-reaction forces through the use of e-rebuttal texts. A mixed-methods approach, incorporating both quantitative and qualitative methods, was employed. The participants included 31 tenth-grade students (15 boys and 16 girls, aged 15-16 years) from a public high school in Sukabumi, West Java, Indonesia. The instrument utilized was a four-tier test consisting of 9 questions related to action-reaction forces: 3 verbal questions for the pre-test, 3 mathematical questions for the post-test (administered after learning), and 3 pictorial questions for the delayed post-test (administered over time). Data were analyzed based on categories of conception and correction of conceptions. The results indicated positive changes from the pre-test to the post-test, which remained consistent in the delayed post-test. The most significant rate of correction in students' conceptions from the pre-test to the post-test was observed in the Acceptable Change (ACh) category, while the highest percentage of changes from the post-test to the delayed post-test occurred in the No Change (NCh) category. It was concluded that e-rebuttal texts effectively reduce students' alternative conceptions (misconceptions) of action-reaction forces both immediately after learning and over time. Future researchers may consider utilizing learning models or strategies that involve group discussions to further facilitate the learning process.